A Community‐Oriented Approach to Breast Cancer in a Low‐Resource Setting: Improving Awareness, Early Detection and Treatment of Breast Cancer in Tajikistan. Issue 3 (May 2016) - Talib, Zohray; Shukurbekova, Irina; Sadonshoeva, Guldarbogh; Alibekov, Alibek; Jamshedov, Nekruz; Moloo, Zahir; Welji, Almas; Amersi, Farin; Muhammad, Aliya Amin; Jiwani, Aliya; Rais, Sheliza; Nazrishoeva, Akoyat; et al.
Abstract: Breast cancer is one of the most common cancers and causes of death in females in Tajikistan; yet less than half of the adult women in Tajikistan have heard of breast cancer. Limited access to health care contributes to late stage presentation. We developed a public–private partnership to implement a breast cancer awareness intervention in a low‐resource community in Khorog, Tajikistan. We trained local health professionals in clinical breast care and conducted a breast cancer screening and treatment program. The partnership involved visiting USA‐based health professionals working alongside local health care providers (HCP) in the continuum of breast care—from education to the diagnostic evaluation and management of detected breast abnormalities. Patient data were collected using a web‐based program (VirtualDoc). Twenty‐four HCP received didactic and clinical breast examination training. 441 women underwent clinical breast evaluation. 74 (17%) had abnormal exams and underwent additional diagnostic procedures. We identified six (1.4%) cases of breast cancer (all locally advanced) and two women had benign fibroadenomas. All women with cancer underwent modified radical mastectomy, while the fibroadenomas were treated by cosmetically appropriate lumpectomy. Five of six subjects with cancer were previously aware of their breast lump and three had recently seen a family medicine (FM) doctor. Health systems assessment revealed availability of diagnostic equipment but lack of well‐trained operators and clinician interpreters. We were successful in integrating clinical breast exams into the routine care of female patients by local FM doctors and in the process, achieved a better understanding of existing risk factors and barriers to breast cancer care. This public–private partnership, leveraging the technical expertise of visiting health professionals, demonstrates how a focused onsite training and awareness program can provide sustained improvements in breast care in a low‐resource environment.